Prevalence, patterns, and factors associated with abnormal lung function among children with sickle cell disease in Uganda: a cross-sectional study - Pamella Mwa Aol; Geriga Fahdil; Felix Bongomin; Bonny Okello; Charles Batte; Bruce J. Kirenga; Rebecca Nantanda; Hellen Tukamuhebwa Aanyu (BMC, 2024)
Abstract Background Pulmonary complications are common among children with sickle cell disease (SCD). However, there is little literature on associated lung function abnormalities in Uganda. We aimed to determine the prevalence, patterns, and factors associated with abnormal lung function among children with SCD in a tertiary care hospital in Uganda. Method A cross-sectional study was conducted among children aged 6 to 18 years at the SCD clinic (SCC) of Mulago National Super-Specialized Hospital between January 2020 and April 2021. Data on sociodemographic and clinical characteristics was collected using a standardized questionnaire. Laboratory investigations, including a complete blood count and serum lactate dehydrogenase (LDH), were done. Spirometry was performed following the ATS/ERS standards. Multivariable modified Poisson regression analysis was performed to determine factors associated with abnormal lung function. Results A total of 332 participants were enrolled. The mean age was 11.7 ± 3.4 years, and 184 (55.4%) were female. Overall, 126 (37.9%) participants had abnormal lung function: 67/126 (53.2%) restrictive, 57/126 (45.2%) obstructive, and 2/126 (1.6%) mixed-ventilatory patterns. Factors associated with abnormal lung function were; serum LDH level > 600UL (aIRR: 1.89 95% CI: 1.2 - 7.4, p = 0.049), a history of acute chest syndrome (aIRR: 1.55, 95% CI: 1.06-2.25, p = 0.024), wasting (aIRR: 1.33, 95%CI: 1.02 - 1.72, p = 0.032), and use of charcoal for household cooking (aIRR: 1.49, 95% CI: 1.03-2.15, p = 0.035). Conclusion More than one-third of children with SCD in Uganda have lung function abnormalities. Strategies to improve nutrition, reduce exposure to charcoal smoke, and monitoring serum LDH levels may be important in preventing or managing abnormal lung function in this population. The identification of reversible and irreversible airway obstruction in children with sickle cell disease also highlights the need for targeted interventions to address these specific patterns of abnormal lung function.